Atomistic theory and simulation of the morphology and structure of ionic nanoparticles - Spagnoli, Dino; Gale, Julian (RSC Publishing, 2012)
Computational techniques are widely used to explore the structure and properties of nanomaterials. This review surveys the application of both quantum mechanical and force field based atomistic simulation methods to nanoparticles, with a particular focus on the methodologies available and the ways in which they can be utilised to study structure, phase stability and morphology. The main focus of this article is on partially ionic materials, from binary semiconductors through to mineral nanoparticles, with more detailed considered of three examples, namely titania, zinc sulphide and calcium carbonate.